FRUGAL LIVING LIFESTYLE OF BENGKULU CITY PEOPLE IN THE REVIEW OF SHARIA ECONOMICS - Efrianto, Eeng Juli; Polindi, Miko; Sari, Nona Febrilia (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
This research is a field research with a qualitative method, conducted in the city of Bengkulu. The informants in this study are the people of Bengkulu city, who were taken by purposive sampling method with indicators of their knowledge and understanding related to the issues being researched. The data in this study consists of primary data and secondary data. The results of this study show that the carried out by the people of Bengkulu can be categorized into a frugal living lifestyle.The frugal living is an extreme frugal lifestyle and allocating their money to more important things for the future such as saving and investing while neglecting consumption. People choose to consume cheap food without knowing the goodness and nutrition contained in it, people’s consumption pattern and more concerned with satiety variables than nutrition. The frugal living community prefer not give infak and give alms because they consider it not mandatory to do so. Every year, they only pay zakat fitrah, even though the property they own meet the requirements and is in harmony for zakat. This is certainly contrary to Islamic consumption ethics which require Muslims to consume halalan tayyiban (halal and good) food, stay away from miserliness, and produce wealth.